Integrating Critical Thinking into Extension Programming #4: Measuring Critical Thinking Styles Using the UFCTI - Alexa J. Lamm (EDIS, 2016)
The fourth installment in the Integrating Critical Thinking into Extension Programming series, this article explains the University of Florida Critical Thinking Inventory (UFCTI), a method of determining a person’s critical thinking style. This 3-page fact sheet describes the history and development of the UFCTI, how to interpret the results, and how to use the test to enhance Extension programs. Written by Alexa J. Lamm and published by the Department of Agricultural Education and Communication, April 2016.